Implementasi Fungsi Sebagai Apoteker Dalam Terapi Pengobatan Swamedikasi Diare Pada Anak Di Sulawesi Selatan - Utami, Yuri Pratiwi; Mustarin, Rahmah; Humang, Rezki Ihsan; Imrawati, Imrawati; Amody, Zahira (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2025)
Diarrhea is one of the main causes of morbidity and mortality in children, especially in areas with limited access to health services. Self-medication is the main alternative for some people, but is often done without adequate understanding. This community service activity aims to improve parents' understanding of self-medication for diarrhea in children and implement the role of pharmacists in providing education and monitoring rational drug use. Activities are carried out in several areas in South Sulawesi through counseling, training, and individual consultations. The results of the activity show an increase in knowledge and more appropriate behavior in the use of antidiarrheal drugs. The implementation of the role of pharmacists has proven effective in encouraging safe and rational self-medication in the community.